Intercontinental comparison of habitat levels of invasion between temperate North America and Europe - Kalusova, Veronika; Chytry, Milan; Peet, Robert K; Wentworth, Thomas R (Ecology, 2015)
Several studies have demonstrated that floras of the New World contain larger proportions of alien species than those of the Old World; however, the differences in fine-scale invasion patterns are poorly known. We compared the levels of invasion in analogous habitats of two environmentally similar regions in temperate North America and Europe (the Carolinas and the Czech Republic), using comprehensive vegetation-plot databases. Native and alien vascular plant species were identified within 4165 vegetation plots assigned to 12 habitats occurring in both areas. The level of invasion was calculated for each habitat (1) as the proportion of aliens recorded cumulatively across multiple plots (habitat scale) and (2) as the mean proportion of aliens per plot (plot scale), both separately for all alien species and for the subgroup of aliens originating in one region and invading the other. The proportions of species native on one continent and invading the other were also calculated for each habitat to compare the alien species exchange between continents. Habitat levels of invasion showed remarkably similar patterns on the two continents. There were significant positive relationships for the levels of invasion, both for all alien species (habitat-scale R2 = 0.907; plot-scale R2 = 0.676) and for those that originated on the opposite continent (habitat-scale R2 = 0.624; plot-scale R2 = 0.708). In both regions, the most and the least invaded habitats were the same, but on average, North American habitats showed higher habitat-scale levels of invasion than their European counterparts. At the same time, a larger proportion of alien species was provided by European habitats for invasion to North America than vice versa. The consistent intercontinental pattern of habitat levels of invasion suggests that these levels are driven by similar mechanisms in distant regions. Habitat conditions are likely to have stronger effect on the level of invasion than the identity of alien species, as shown by similar levels of invasion in analogous habitats despite different geographical origins of alien species. The higher flux of alien species from Europe to North America is consistent with a generally higher level of invasion of North American habitats.
Keywords: Severní Karolína; Česká republika; rostliny; North Carolina; Jižní Karolína; ekosystém; Czech Republic; Plants; South Carolina; podnebí; zavlečené druhy; Climate; Ecosystem; Introduced Species